101k views
1 vote
Rewritten in vertex form please!!! Asap!!!

Rewritten in vertex form please!!! Asap!!!-example-1
User Calumb
by
6.1k points

2 Answers

2 votes

Answer:

B

Explanation:

The equation of a parabola in vertex form is

y = a(x - h)² + k

where (h, k) are the coordinates of the vertex and a is a multiplier

Given

y = (x + 3)² + (x + 4)² ← expand and simplify

= x² + 6x + 9 + x² + 8x + 16

= 2x² + 14x + 25

To obtain vertex form use the method of completing the square

The coefficient of the x² term must be 1

Factor out 2 from 2x² + 14x

y = 2(x² + 7x) + 25

add/ subtract ( half the coefficient of the x- term )² to x² + 7x

y = 2(x² + 2(
(7)/(2)) x +
(49)/(4) -
(49)/(4) ) + 25

y = 2(x +
(7)/(2) )² -
(49)/(2) +
(50)/(2)

y = 2(x +
(7)/(2) )² +
(1)/(2)

User JayK
by
6.2k points
5 votes

Answer:

vertex form:
y=2(x+(7)/(2))^2+(1)/(2)

B correct

Explanation:


y=(x+3)^2+(x+4)^2


y=x^2+9+6x+x^2+16+8x


y=2x^2+14x+25


y=2(x^2+7x)+25


y=2(x^2+7x+(49)/(4)-(49)/(4))+25


y=2(x+(7)/(2))^2+(1)/(2)

User Martin Ender
by
5.5k points